DEVELOPING A MODEL OF SN-PT-BASED INTERNAL ACADEMIC QUALITY ASSURANCE SYSTEM IN THE EDUCATIONAL TRAINING INSTITUTION OF THE MILITARY ACADEMY MAGELANG - Kurniatun, Endang Sri; Rachman, Maman; Masrukhi, Masrukhi; Rusdarti, Rusdarti (The Journal of Educational Development, 2017)
Military Academy is an educational training institution in the field of defense, which implements the changes of the quality assurance system based on the ten components of the Army education to the internal academic quality assurance system that is based on the Higher Education National Standards (SN-PT). Military Academy requires strengthening to find a model of appropriate quality assurance system in order to be accreditable by the National Accreditation Board of Higher Education. This study aims to (1) analyze the current quality assurance system in the Military Academy; (2) develop an appropriate SN-PT based model of internal academic quality assurance system in the Military Academy; (3) examine the feasibility of the appropriate SN-PT based internal academic quality assurance system in the Military Academy. This study implemented a research and development approach, employing data sourced from the informants, events and documents. The data were drawn through interviews, observation, and documentation; its validity was tested by tools and resources triangulation. The data were then analyszed using interactive techniques with reduction, display, and conclusion steps. The results of the study: (1) the quality assurance system in the Military Academy is running properly but it still requires further development; (2) the SN-PT based of internal academic quality assurance system implemented in the Military Academy uses the 10 basic education components retained by elaboration, little changes, and additions, related to general quality standards of the SN-PT, including the organizational structure, standards of academic quality, mechanism of the quality assurance system, and SN-PT based internal academic quality assurance system. (3) The results of the feasibility studies indicate that the development of the SN-PT based internal academic quality assurance system model in the Military Academy Magelang is feasible and appropriate. Conclusion: Military Academy requires development in terms of organizational structure quality assurance, academic quality standards, quality assurance mechanisms, and internal academic quality assurance system based